A Rare Case of Eisenmenger Syndrome Complicated by Dengue Hemorrhagic Fever - Felly Moelyadi; Hendrata Erry Andisari (MEDICINUS, 2026)
Background: Eisenmenger syndrome (ES) is a rare complication of congenital heart disease characterized by pulmonary hypertension and bidirectional or reversed shunt. Patients with ES are vulnerable to infections, including dengue virus(DENV), which can further aggravate cardiovascular compromise. Case: A 32-year-old woman with a history of congenital heart disease was admitted with shortness of breath, cyanosis, palpitations, and vomiting. During hospitalization, patientsdeveloped fever, rash, petechiae, and thrombocytopenia. Echocardiography demonstrated an atrial septal defect withbidirectional shunt and pulmonary hypertension, consistent with ES. Laboratory results confirmed dengue hemorrhagic fever (DHF) with hemoconcentration and severe thrombocytopenia. Management included cautious fluid resuscitation,platelet transfusion, corticosteroids, and supportive therapy with sildenafil citrate for pulmonary hypertension. Clinical improvement was achieved, and the patient was discharged after nine days of hospitalization. Conclusion: Thiscase illustrates the complex interaction between ES and DHF, in which increased vascular permeability, coagulation abnormalities, and chronic hypoxemia exacerbate hemodynamic instability. Currently, there are no standardized guidelines for managing dengue in patients with ES; therefore, therapy must be individualized with vigilant monitoring. Recognition of this rare comorbidity is important to prevent complications, optimize treatment, and improve survival.